Mastering Automation Tools for Incident Management and Monitoring - Jugnu Misal, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the evolution and implementation of modern automation and monitoring tools in enterprise environments. The article explores four key areas: enterprise automation frameworks, Prometheus monitoring capabilities, Nagios infrastructure monitoring, and Datadog observability solutions. Through a detailed examination of implementation methodologies, performance metrics, and operational impacts, this article provides insights into how organizations can optimize their IT operations through intelligent automation and monitoring. The article encompasses advanced features, including machine learning integration, anomaly detection, predictive analytics, and automated incident management, while also addressing the importance of proper implementation strategies and best practices. The article further investigates the role of AIOps in transforming traditional IT operations and explores the significance of maintaining development environments through home lab setups.
Keywords: Infrastructure Monitoring; Enterprise Automation; AIOps Integration; Cloud-Native Observability; Incident Management Systems